A role for the auxin precursor anthranilic acid in root gravitropism via regulation of PIN-FORMED protein polarity and relocalisation in Arabidopsis - Doyle, Siamsa M; Rigal, Adeline; Grones, Peter; Karady, Michal; Barange, Deepak K; Majda, Mateusz; Pařízková, Barbora; Karampelias, Michael; Zwiewka, Marta; Pěnčík, Aleš; Almqvist, Fredrik; Ljung, Karin; et al. (The New phytologist, 2019)
distribution of auxin within plant tissues is of great importance for developmental plasticity, including root gravitropic growth. Auxin flow is directed by the subcellular polar distribution and dynamic relocalisation of auxin transporters such as the PIN-FORMED (PIN) efflux carriers, which can be influenced by the main natural plant auxin indole-3-acetic acid (IAA). Anthranilic acid (AA) is an important early precursor of IAA and previously published studies with AA analogues have suggested that AA may also regulate PIN localisation. Using Arabidopsis thaliana as a model species, we studied an AA-deficient mutant displaying agravitropic root growth, treated seedlings with AA and AA analogues and transformed lines to over-produce AA while inhibiting its conversion to downstream IAA precursors. We showed that AA rescues root gravitropic growth in the AA-deficient mutant at concentrations that do not rescue IAA levels. Overproduction of AA affects root gravitropism without affecting IAA levels. Treatments with, or deficiency in, AA result in defects in PIN polarity and gravistimulus-induced PIN relocalisation in root cells. Our results revealed a previously unknown role for AA in the regulation of PIN subcellular localisation and dynamics involved in root gravitropism, which is independent of its better known role in IAA biosynthesis.
Keywords: mutace; chinolony; Quinolones; Arabidopsis Proteins; Indoleacetic Acids; Mutation; proteiny huseníčku; ortho-Aminobenzoates; PIN-FORMED proteins; PIN polarity; root gravitropism; polarita buněk; Plant Roots; kyseliny indoloctové; anthranilic acid (AA); Arabidopsis thaliana; Cell Polarity; auxin transport; Arabidopsis; kořeny rostlin; Gravitropism; gravitropismus; ortoaminobenzoáty